Escurrimiento, sedimentos y elementos asociados en distintos ambientes de la Pampa Ondulada - Darder, Maria Liliana; Castiglioni, Mario Guillermo; Caprile, Ana Clara; Spinazzola, Emilio Miguel; Llorente, Ricardo Teodoro (Asociación Argentina Ciencia del Suelo, 2021)
Poster